KUALITAS LAYANAN E-GOVERNMENT PADA PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANYUMAS - Thahrina Azriah; Farchah Naelyatara (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
The purpose of this study was to describe the quality of E-Government in citizenship administrative service of Population and Civil Registry Office of Banyumas Regency. The citizenship administrative service can be accessed by the public through the gratiskabeh.banyumaskab.go.id. website. This study used quantitative research method and cluster sampling technique. The respondents of this study were 100 people. They were the users of this website service. Methods of data collection used questionnaire, observation, and documentation. The result obtained shows that the quality of E-Government in citizenship administrative services through the gratiskabeh.banyumaskab.go.id. website had been optimal in four dimensions, which were efficiency, trust, reliability, and citizen support.